EFFECTS OF A MULTICOMPONENT BALANCE AND STRENGTH TRAINING PROGRAM ON POSTURAL STABILITY IN OLDER ADULTS: A REPEATED-MEASURES ANALYSIS - ENACHE, Alexandru-Valentin; CHEPTĂNARU, Daniela; GEIGER, Evelyne; VĂDAN, Anca-Lucia (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Aging is characterized by a progressive decline in balance and mobility, leading to an increased risk of falls among older adults. This pilot study investigated the effects of a multicomponent balance and strength training program on postural control in community-dwelling older adults. Four participants (two men, two women; age 72–94 years, M = 79.0, SD = 9.9) completed a 6-week intervention consisting of thrice-weekly sessions (20–25 minutes, light-to-moderate intensity) including warm-up, progressive balance/strength exercises and cool-down. Postural stability was assessed using a BTS P-WALK baropodometric platform under six conditions: quiet standing and half-squat position with eyes open then closed, each on hard and soft surfaces. Thirty-six center-of-pressure variables (area, path length, velocity) were analyzed at three time points (baseline, intermediate, final). Given the small sample size (N = 4) and some non-normally distributed variables, Friedman’s test was used. No statistically significant differences were found across time (all p ≥ .105). However, descriptive trends indicated modest improvements in sway area, path length, and velocity under eyes-open and half-squat conditions, suggesting enhanced postural stability. Although underpowered, this study highlights the feasibility of implementing multicomponent balance training in older adults and suggests potential benefits for fall prevention. The absence of decline in postural stability itself may be clinically relevant. Future larger-scale trials with longer follow-up are needed to confirm these findings and to explore whether improvements in force-platform metrics translate into meaningful reductions in fall risk.